New Pathways for Community Energy and Storage - Windt, Henny J. van der; Oost, Ellen van; Koirala, Binod; Waal, Esther van der (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Local communities are increasingly taking on active roles and emerging as new actors in energy systems. Community energy and energy storage may enable effective energy system integration and ensure maximum benefits of local generation, leading to more flexible and resilient energy supply systems and playing an important role in achieving renewable energy and climate policy objectives. In this book, we summarize the different topics covered in the international conference on new pathways for community energy and storage in the form of the 14 articles published in this Special Issue on the same topic. It addresses important developments and challenges related to local energy transitions and the role of community energy and energy storage therein.